Peranan Tata Tertib Sekolah Terhadap Pembentukan Karakter Pancasila Siswa Di Madrasah Aliyah Bustanul Muta’allimin Kota Blitar - Laila Rofi’atun Nisa; Arik Cahyani; Ida Putri Rarasati (Berugak Baca, 2024)
Education is something that never stops developing and always raises many different problems. As technology and communication develop, school-age children, especially teenagers at the SMA/MA level who are still searching for their identity, are very vulnerable to the problems of globalization and the decline in morality. There are 3 data collections used in this research plan, namely interviews, observation and documentation. From the results of research using descriptive analysis, it was found that students at MA Bustanul Muta'alimin, Blitar City, still lack aspects of time discipline and often ignore school rules. So the implementation of school rules and regulations at MA Bustanul Muta'allimin Blitar City is in the medium category.4. MA Bustanul Muta'allimin Blitar City. Teachers play an important role in enforcing rules and regulations at school and are responsible for educating students to make them better. Everything a teacher does at school should be interpreted as part of the educational process, teachers as examples and role models for students.